Lifelong Learning Goes to the Movies: Autobiographical Narratives as Media Production - Nod Miller (Adult Education Research Conference, 2000)
A blockbuster of a paper (nominated for Best Foreign Contribution) in which the heroine describes a perilous path through the territory of narrative theory and text construction. She encounters the threshold guardians of writer’s block and self-doubt, wrestles with shapeshifters, tricksters and shadows, rallies after encounters with mentors and allies and returns to the ordinary world with the elixir of lifelong learning (or, at least, a completed conference paper).